Integrating Extended Reality (XR) in Architectural Design Education: A Systematic Review and Case Study at Southeast University (China) - Yueying Zhang; Xiaoran Huang (Buildings)
In recent years, extended reality (XR) technologies have emerged as transformative tools within the architectural design industry, offering immersive and interactive environments that enhance visualisation and collaboration. However, a significant gap remains between adopting these technologies in professional practises and integrating them into architectural design education. This study aims to bridge this gap by systematically reviewing XR applications in architectural design practises and exploring their potential integration into design studios. It specifically focuses on undergraduate graduation projects from the School of Architecture at Southeast University in China. Findings indicate that XR can transform traditional design approaches by refining design methods, extending design scopes, and encouraging the inclusion of diverse stakeholders. The paper also offers insights into optimising XR applications in architectural design education, providing strategic recommendations for technical advancements and academic curricula innovation, ultimately preparing students for technology-driven changes in professional practises.